STOCK PRICE REACTION TO THE ANNOUNCEMENT OF STOCK SPLIT AT MANUFACTURING COMPANIES IN JAKARTA STOCK EXCHANGE: ABNORMAL RETURN ANLYSIS USING BETA CORECTION - Pamungkas, R. Sadha; H. Supardi, Drs. (Accounting, 2009)
Stock split is phenomenon that still becoming puzzle in economics. Stock split usually occur after a significance increase in stock price and usually elicit a positive stock price reaction upon announcement. The reason for this reaction has not been clearly understood. According to the problem, this study is designed to examines the stock price reaction to the announcement of stock split, initially doing a correction toward bias beta uses four lags and four leads Fowler and Rorke method. The collecting data uses purposive sampling. Sample consists of 30 stocks performing the stock split during the period of 1998 to 2003. The test done using kolmogorov-smirnov test to determine data’s normality, and paired sample t-test to test signification abnormal return before and after announcement. From the result, can be conclude that no significant differences in company’s abnormal return, before and after announcement. Whereas from the result reaction stock price shown that stock split announcement give a significant reaction in the first day after announcement, but the reaction is negative. Key words : Stock split, abnormal return, stock price, beta correction.